Social Media as A Tool for Improving Pronunciation Skills in French among Selected English-Speaking Students at the Federal Polytechnic Ilaro Ogun State Nigeria - Olaoye, Olatunji Adetunji; Onipede, Festus Moses (English Department, Faculty of Humanities, Andalas University, 2025)
This study examines how well the selected National Diploma and Higher National Diploma students doing French courses at the Federal Polytechnic Ilaro in Ogun State, Nigeria, can pronounce French words correctly by using social media as a tool. The study aims to determine the following: 1) how well English-speaking students at the Federal Polytechnic Ilaro can pronounce French words correctly; 2) how the students feel about using social media as an additional tool for learning French pronunciation; and 3) which social media practices and strategies work best for helping English-speaking students pronounce French words correctly. Six hundred (600) students in all (School of Engineering, School of Pure and Applied Science, School of Communication and Information Technology, School of Environmental Studies, and School of Agriculture, School of Management studies), split equally between the experimental and control groups, took part in the study. While the control group practiced pronunciation using conventional means, the experimental group used social media platforms. To identify notable changes, frequency, percentage, and chi-square tests were used to analyse the pre- and post-test scores. The experimental group's results show a significant improvement, indicating that social media can be a useful tool for language learning.